PENGARUH PROFITABILITAS, STRUKTUR MODAL DAN LIKUIDITAS TERHADAP HARGA SAHAM PERUSAHAAN SUB SEKTOR TRANSPORTASI YANG TERDAFTAR DI BEI TAHUN 2012-2017 - Dewi Mutia; Syamwil Syamwil; Abel Tasman (Jurnal Ecogen, 2018)
This articel is aimed to inform the effect of profitability, capital structure and liquidity to  stock price on transportation company sub sector listed on Indonesian Stock Exchange within period 2012-2017. The research method in this study is an causal comparative. The population amounts to 32 companies with amount 192 data. Based on sampling technique purposive sampling researcher used 9 companies with amount 37 data that meets the criteria with variabel Return On Equity (ROE), Debt to Equity Ratio (DER) and Current Ratio (CR). All the data analyze using statistical descriptive analysis and regression analysis with SPSSs.The results showed that simultaneous ROE, DER, and CR significantly influence stock prices. Partially, ROE is a variable that has positive and significant impact on stock prices, while the DER and CR is partially has negative but not significant effect on stock prices.Keyword: profitability, capital structure, liquidity,  and stock price